Think and grow rich - Hill, Napoleon (New York Penguin, 2005)
Think and Grow Rich has been called the "Granddaddy of All Motivational Literature." It was the first book to boldly ask, "What makes a winner?" The man who asked and listened for the answer, Napoleon Hill, is now counted in the top ranks of the world's winners himself.
Includes index
Keywords: Carnegie, Andrew, 1835-1919.